(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Religious changes are an unavoidable part of social life that follows the progression of social history. The religious lives of the ethnic minorities in the Central Highlands are changing in a variety of ways and at various levels. This article uses analytical and synthetic research methodologies to examine the following aspects of the ethnic minorities’ religious lives in the Central Highlands: the significant shift from polytheism to monotheism and religious diversity; transformation of religious beliefs and practices; transformation of ecclesiastical institutions and communities in religions. Thereby, the face of beliefs and religious lives, as well as the impact of religious transformation on the lives of ethnic minorities in the Central Highlands of Vietnam today has been clarified.